Digital Transformation and Sustainability Governance in Industrial Ecosystems: A Conceptual Framework for Industrial Estates - Didik Prasetiyono; Ahmad Yusri Authoni; Rafika Nur Kusumawati (Journal of Strategic Innovation and Business Management, 2026)
Industrial estates are increasingly expected to support not only industrial growth but also sustainability environmental accountability, and coordinated infrastructure management. At the same time, digital transformation is reshaping how industrial actors generate information, monitor shared systems, and coordinate activity across complex industrial environments. Although sustainability governance, digital transformation, and industrial ecosystem governance have each received substantial scholarly attention, these streams remain weakly integrated, particularly in explaining how digital systems can strengthen governance where sustainability challenges are distributed across multiple actors, shared infrastructures, and institutional levels. Addressing this gap, this study develops a conceptual framework for digital sustainability governance in industrial ecosystems, with particular relevance to industrial estates in emerging economies. Using a structured literature-synthesis approach, the study proposes a Smart Digital Sustainability Governance Model composed of four interrelated pillars: governance leadership, digital sustainability infrastructure, industrial ecosystem collaboration, and institutional policy alignment. The framework argues that sustainability governance in industrial estates depends not only on firm-level ESG commitments, but also on estate-level leadership, digitally enabled monitoring and information infrastructures, cross-actor coordination, and alignment with broader institutional and policy structures. Indonesia, with reference to Surabaya Industrial Estate Rungkut (SIER), is used as a contextual illustration. The study contributes by extending sustainability governance from the firm level to the ecosystem level and by repositioning digital transformation as a governance-enabling mechanism in complex industrial environments.